Fertility, agricultural labor supply, and production: Instrumental variable evidence from Uganda - Van Campenhout, Bjorn (Cambridge University Press, 2016)
Human fertility can affect agricultural production through its effect on supply of agricultural labor. Using the fact that in traditional, patriarchal societies, sons are generally preferred to daughters, we isolate exogenous variation in the number of children born to a mother and relate it to the agricultural labor supply and production in Uganda, which has a dominant agricultural sector and high fertility. We find that fertility has a sizable negative effect on household labor allocation to subsistence agriculture. Households with lower fertility devote significantly more time to land preparation and weeding; larger households grow less matooke and sweet potatoes. We find no significant effect on agricultural productivity in terms of yield per land area.